2001
DOI: 10.4049/jimmunol.166.8.4931
|View full text |Cite
|
Sign up to set email alerts
|

CD99 Signals Caspase-Independent T Cell Death

Abstract: Death signaling by Fas and TNF receptors plays a major role in the control of activated mature T cells. However, the nature of the death receptors, which may be used by the immune system to control T cells that have not acquired susceptibility to Fas ligand or TNF, is not established. In this study, we demonstrate that engagement of distinct epitopes on CD99 rapidly induces T cell death by a novel caspase-independent pathway. A new mAb to these CD99 epitopes, Ad20, induces programmed cell death of transformed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
95
1
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(100 citation statements)
references
References 91 publications
3
95
1
1
Order By: Relevance
“…Similar results were observed for CD8 ϩ T cells specific for the remaining three epitopes shown in Fig. 4, and also for CD4 ϩ T cells specific for the GP 61 and NP 309 epitopes (not shown). Any differences observed were not statistically significant.…”
Section: Eleven Different Zvad Regimens Fail To Significantly Change supporting
confidence: 73%
See 1 more Smart Citation
“…Similar results were observed for CD8 ϩ T cells specific for the remaining three epitopes shown in Fig. 4, and also for CD4 ϩ T cells specific for the GP 61 and NP 309 epitopes (not shown). Any differences observed were not statistically significant.…”
Section: Eleven Different Zvad Regimens Fail To Significantly Change supporting
confidence: 73%
“…In brief, cells from blood, lymph nodes, or spleens of LCMV-infected or naive mice were isolated as described above, then were incubated in round-bottom 96-well plates at 37°C, 5% CO 2 , for 5-7 h in the presence or absence of peptide in RPMI 1640 (containing 5-10% FBS, 100 M 2-ME, L-glutamine, and antibiotics). The peptides, used at a final concentration of 1-2 g/ml, represent dominant and subdominant CD8 ϩ T cell epitopes from LCMV: NP 118 [61][62][63][64][65][66][67][68][69][70][71][72][73][74][75][76][77][78][79][80] and NP 309 -328 (both H-2A b ). Brefeldin A (Sigma) was added to a final concentration of 5 g/ml.…”
Section: Intracellular Cytokine Staining (Iccs)mentioning
confidence: 99%
“…It has been suggested that the PARs may harbor genes for other psychiatric disorders including schizophrenia and bipolar affective disorders [Crow et al, 1994;Saito et al, 2000;Muller et al, 2002;Lencz et al, 2007]; however, they have been largely neglected in systematic genome-wide linkage and association studies [Flaquer et al, 2008[Flaquer et al, , 2009. For example, the Illumina HumanHap550 genotyping platform does not include any SNP markers in the PAR1 region in or near XG/ XGPY2 at chromosome Xp22.33/ Yp11.31 where our novel significant association signal was identified.The XG gene encodes human red blood cell Xg a antigen and is tightly linked to an adjacent gene, CD99, which encodes CD99 antigen, a T-cell surface protein, expressed on all leukocytes, which plays an important role in immunology, including leukocyte migration and activation, T-cell adhesion, and caspase-independent T-cell death [Hahn et al, 1997;Pettersen et al, 2001;Oh et al, 2007;Dufour et al, 2008]. There is emerging evidence that an abnormal immune response may be involved in some forms of ASD, in the form of decreased peripheral lymphocyte counts, incomplete T cell activation, dysregulated apoptosis mechanisms, and imbalanced serum Ig levels [Ashwood et al, 2006].…”
mentioning
confidence: 99%
“…Originally, CD99 was described as a human thymus leukemia antigen, Ewing's sarcomaspecific membrane marker molecule, and a putative adhesion molecule (termed E2) involved in spontaneous rosette formation of T cells with erythrocytes (Bernard et al, 1988;Aubrit et al, 1989;Gelin et al, 1989). In the studies using monoclonal antibodies (mAbs) against CD99 as stimulatory ligands, engagement of CD99 led to homotypic aggregation and death of thymocytes and Jurkat T cells (Bernard et al, 1995;Bernard et al, 1997;Hahn et al, 1997;Pettersen et al, 2001) and induced up-regulation of T cell receptor (Waclavic et al, 1998) and major histocompatibility complex molecules on the cell surface (Choi et al, 1998;Kim et al, 2003).…”
Section: Introductionmentioning
confidence: 99%